Analysis of tourists' perception during 2014 World Cup in Brazil - Lohmann, Paola Bastos (2015)
This article aims to analyze, in a comparative way, the perception of national and international tourists regarding the impacts generated by the 2014 FIFA World Cup on tourism in the host cities, in the period of the event. The methodology of data collection was a survey research, conducted in the period from June 12 to July 14, 2014 in all 12 host cities of the event, with a total of 2678 domestic and 872 international respondents. The research objectives are to detail the travel characteristics, the respondent profile, and perception of the positive and negative impacts of the event. As a result it will be possible to analyze the characteristics of tourists who travel to attend sporting event in Brazil and profit the experience as a reference for the Olympics and for the country as a whole. The data indicate that for domestic tourism the World Cup had a family atmosphere and for international tourists it was an opportunity to attend the event and also to know the country. From the perspective of both, the Brazilian and foreign, the stimulus to tourism and the possibility of increasing the visibility of destination are the main positive aspects to host the World Cup in the country. The negative aspects are more specific to foreigners, issues related to travel, such as distance between the host cities, high prices, lack of tickets, public transportation, disorganization, followed by the issues raised in the first place by the national respondents, which are related to excessive public spending and financial mismanagement. (C) 2014 The Authors. Published by Elsevier B. V.